2002
DOI: 10.1001/archinte.162.7.786
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Seropositivity and Systemic and Renovascular Atherosclerotic Disease

Abstract: The presence of antibodies to C pneumoniae was significantly associated with atherosclerosis and renovascular disease in hypertensive patients in whom a renal artery stenosis was strongly suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A meta‐analysis of six studies found an adjusted odds ratio of only 1.2 (95% confidence interval, 1.0–1.5) for the development of CAD in seropositive subjects. 12 Seropositivity to C. pneumoniae is highly prevalent within the general population (up to 70% even in the absence of atherosclerosis), 13 diminishing the utility of antibody testing. Traditionally, seropositivity has been defined as ≥1:8 or ≥1:16.…”
Section: Potential Role Of Infection In Atherogenesismentioning
confidence: 99%
“…A meta‐analysis of six studies found an adjusted odds ratio of only 1.2 (95% confidence interval, 1.0–1.5) for the development of CAD in seropositive subjects. 12 Seropositivity to C. pneumoniae is highly prevalent within the general population (up to 70% even in the absence of atherosclerosis), 13 diminishing the utility of antibody testing. Traditionally, seropositivity has been defined as ≥1:8 or ≥1:16.…”
Section: Potential Role Of Infection In Atherogenesismentioning
confidence: 99%
“…14 Possible mechanisms involved are (1) hypertrophy and proliferation of the smooth muscle cells and (2) a pathologically modified extracellular matrix. 15,16 Studies investigating the association between C pneumoniae and hypertension reported increased antichlamydial antibodies among hypertensive patients with atherosclerosis and renovascular disease or severe essential hypertension; 17,18 however, in a large prospective trial, no significant interrelationship was found. 19 The influence of age on IMT was similarly strong in our general population survey.…”
Section: Discussionmentioning
confidence: 99%